Complex for acquaintance with global culture: designing the proposed Bishwa Shahitta Kendra Cultural Complex - Bhuiyan, Tanjimul Amin (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2016.